Cutaneous melanoma in the State of São Paulo: a spatial approach - Camila Trolez Amancio; Luiz Fernando Costa Nascimento (Anais Brasileiros de Dermatologia, 2014)
BACKGROUND:Cutaneous melanoma is a skin cancer with low incidence but high mortality rates. Several factors are associated with increased risk of melanoma, such as excessive sun exposure, fair skin, and family history, among others. Little is known about the spatial distribution of this cancer in Brazil.OBJECTIVE:To identify, through the use of geostatistical tools, spatial clusters of municipalities in the state of São Paulo based on their incidence of cutaneous melanoma.METHODS:This was an ecological and exploratory study of data on new cases obtained from Fundação Oncocentro for the period 1 January 2006-31 December 2011. Cases were separated by gender and rates per 100,000 inhabitants were calculated and used to compile thematic maps, Moran maps and kernel maps, using TerraView software.RESULTS:There were 3,172 new cases of cutaneous melanoma in the study period. High rates were identified in the North, Northwest, Southwest, and Southeast regions of São Paulo state. Global Moran's I values were statistically significant (p<0.05) at 0.12, 0.08, and 0.16, respectively, for males, females, and all cases. Areas such as the Southeast, North, and Northwest of São Paulo were identified as being of high priority for intervention.CONCLUSION: Spatial clusters of municipalities with high incidence rates of cutaneous melanoma in the state of São Paulo were identified. These data can serve as an important input for public health agencies.